2015
DOI: 10.1080/09168451.2015.1034652
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid enhances endurance capacity of exercise-trained mice by increasing skeletal muscle oxidative properties

Abstract: (2015) Acetic acid enhances endurance capacity of exercise-trained mice by increasing skeletal muscle oxidative properties, Bioscience, Biotechnology, and Biochemistry, 79:9, 1535-1541,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 50 publications
0
31
3
Order By: Relevance
“…However, other fibrolytic bacteria like Fibrobacter along with the Treponema , a hydrogen utilizing microorganism that work with fibrolytic bacteria 23 , were much higher in community type 1 compared to type 2 and were in line with results from other studies 40 , suggesting that the community type 1 harbored less complex but more specialized microbiota to produce acetate as a mean of maintaining the energy supply as the glucose concentrations fell during the race. Pan and colleagues 41 showed that acetic acid enhanced endurance performance in exercise-trained mice by inducing enzymes involved in fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, other fibrolytic bacteria like Fibrobacter along with the Treponema , a hydrogen utilizing microorganism that work with fibrolytic bacteria 23 , were much higher in community type 1 compared to type 2 and were in line with results from other studies 40 , suggesting that the community type 1 harbored less complex but more specialized microbiota to produce acetate as a mean of maintaining the energy supply as the glucose concentrations fell during the race. Pan and colleagues 41 showed that acetic acid enhanced endurance performance in exercise-trained mice by inducing enzymes involved in fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that bilirubin activation of PPARα induces mitochondrial function [ 20 ], and that mice with the loss of BVRA have reduced mitochondrial function [ 38 ]. Therefore, we measured citric acid and acetic acid in the HCR and LCR rats, two metabolites associated with mitochondrial activity [ 39 , 40 , 41 ]. The HCR rats had significantly increased levels of citric acid and acetic acid ( Figure 6 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…However, studies on the effects of probiotics on muscle mass and function have been scarcely reported, and the potential effects of probiotics on physical performance and their underlying mechanisms remain unclear. Few studies have suggested the potential impact of probiotics on the gut microbiomes of athletes [9], and the possible involvement of metabolites of gut microbiota, such as acetic acid, in the stimulation of muscular energy metabolism [10], and the enhancement of endurance performance [11].…”
Section: Introductionmentioning
confidence: 99%